Degradation of Aluminide Coatings Deposited on Nickel Superalloys. (2016) - Kianicová, Marta; Kafrík, Ján; Trník, Jaroslav
Abstract: Cyclic oxidation and hot corrosion behaviours of aluminide and Si modified aluminide diffusion coatings deposited on two superalloys are compared in the paper. Samples based on cast nickel superalloys with and without protective coatings were studied under cyclic oxidation and hot corrosion conditions. The main goal of the paper was to compare the cyclic oxidation and hot corrosion resistance of protective aluminide coatings deposited on two types of nickel superalloys, Inconel 713LC and MAR-M247. All samples were exposed to cyclic oxidation and hot corrosion environment at Silesian University of Technology in Katowice, Poland. Hitachi SEM with EDS microanalysis was used for analysis of surfaces and cross-sections of the samples. Experimental cyclic oxidation test was carried out in inductive furnace at 1100 °C and samples were exposed to 24 cycles. Heating time took 23 h. After each oxidation cycle, the samples were taken out of furnace and cooled in the air. Mass changes of the samples were written down during each second cycle to observe the progress of cyclic oxidation. The resulting graph of the sample masses revealed that resistance to cyclic oxidation of IN713 LC samples without protective coating exposed to 24 cycles was very good and without any noticeable damage. The oxidation of the superalloy surface of MAR-M247 without the protective coating was very fast. Hot corrosion is the accelerated oxidation of a material at elevated temperature induced by a thin film of fused salt deposit. Superalloys samples were coated by help of the method out-of-pack. Corrosive environment was created using tablets of Na2 SO4 at temperature 920 °C. Results of tested samples revealed that the samples with Si modified aluminide coating had the highest life-time.